P172 Clinical characteristics of newly diagnosed adult patients with Crohn's disease in Japan: Interim analysis of Inception cohort registry study of patients with Crohn's disease (iCREST-CD). (27th May 2021) - Matsuoka, K; Fujii, T; Okamoto, R; Yamada, A; Kunisaki, R; Matsuura, M; Watanabe, K; Shiga, H; Takatsu, N; Bamba, S; Mikami, Y; Yamamoto, T; et al.
Abstract: Background: Information on patient demographics and disease characteristics at the time of Crohn's disease (CD) diagnosis is considered to be an important aspect in the treatment and management of CD. However, reports on phenotypes, disease course, and treatment impact in newly diagnosed CD patients are limited. An interim analysis of a large registry study was conducted to analyze the clinical characteristics of CD patients at the time of diagnosis. Methods: This prospective, non-interventional, observational registry study was conducted at 19 tertiary centers for CD treatment in Japan. Patients newly diagnosed with CD after Jun 2016 based on diagnostic criteria of the Ministry of Health, Labour & Welfare of Japan (age ≥16 years (yrs) at the time of informed consent with no prior exposure to biologics) were enrolled. Patient demographics, diagnostic procedures and categories, disease location and behavior of the lesions (based on Montreal classification) at time of CD diagnosis, were recorded. Results: Patients were enrolled between Dec 17, 2018 and Jun 30, 2020, and a total of 672 eligible patients were analyzed; 93.3% (n=627) had definitive diagnosis and 68.2% were men. At the time of diagnosis, median age was 25 (range 13–86) yrs, and peak disease onset was 20–24 yrs. Diagnostic imaging examinations included conventional ileocolonoscopy (542/665, 81.5%), esophagogastroduodenoscopy (413/665, 62.1%), small bowel capsule endoscopy (74/665, 11.1%), balloon-assisted enteroscopy (149/665, 22.4%), CT enterography (74/665, 11.1%), and MR enterography (45/665, 6.8%). Most common disease location was L3 (ileocolonic), followed by, L1 (ileal) and L2 (colonic), 60.1%, 22.7%, and 16.3% of 664, respectively. Nonstricturing/nonpenetrating disease (B1) was most common behavior, followed by stricturing (B2) and penetrating disease (B3), 62.8%, 25.8% and 10.7% of 662, respectively; perianal disease was seen in 48.9% of 662. Interestingly, disease phenotype was different between the different age-at-onset groups (A1 [≤16 yrs], A2 [17–39 yrs], A3 [40–64 yrs], and elderly defined by age of onset ≥65 yrs; Figure 1–3). The male-to-female ratios were also different between these groups (A1: 1.7, A2: 2.6, A3: 1.3 and elderly: 1.3). Conclusion: The study provides novel prospective insight on the clinical characteristics of newly diagnosed CD patients. Disease phenotype varied between patients <40 yrs and those ≥40 yrs of age in terms of male-to-female ratios, disease location/disease behavior/presence or absence of perianal lesion at the time of diagnosis. The ongoing prospective follow-up will provide additional insight.